The impact of shallow streams on the surface horizons of typical chernozem with different erosion degree - O. O. Plotnikova; V. V. Demidov; M. P. Lebedeva (Бюллетень Почвенного института им. В.В. Докучаева, 2018)
The rill erosion affects significantly on the processes of arable soils degradation. Therefore the aim of the work was to continue the development of hydraulic and statistical methods for assessing the transportation of soil material by shallow streams. For this purposes, we conducted the verification of shallow water flows transporting capacity equation. As an object we used typical chernozems with medium depth light clay loamy on loess like clay loams deeply tilled non-eroded, weakly eroded and medium eroded. Samples for the purposes of the study were collected in the Kursk region. The comparison of the experimental and calculated by the equation turbidity values showed a satisfactory correspondence. The average relative error of calculations contained in modulo 18.0%, and the correlation coefficient was 0.89. The model experiment on a large erosion flume, revealed that the weighted average diameter of the aggregates moved by the flow is increased as the flow velocity is also increased. However, the diameter of aggregates deposited in the bed is decreased. This regularity was revealed as with air-dry initial state of the samples and with capillary-moistened initial state. It was found that the water flow with the low speed (0.3915 m/s) first of all washes out the multi-ordered and the densiest humified aggregates (including coprolites), whereas the pieces of less humified aggregates and separate mineral grains are accumulated on the bed. We revealed that this is quite specific for both types of the initial states of the samples. It was noted that the fractions sizes of the aggregates washed out by the flow at both initial states of the samples are congruent; the same is true for aggregates deposited in the channel